Impact of Covid-19 pandemic on the mortality in Republic of North Macedonia - Janeska, Verica; Lozanoska, Aleksandra (Institute of Economics - Skopje, 2022)
The aim of the paper is to determine the impact of the Covid-19 pandemic on the mortality in Republic of North Macedonia. In terms of identifying the influence of Covid-19 on mortality changes, demographic and other features, as well as causes of death, are analyzed in pre-pandemic and in 2020-2021. The available data of State Statistical Office, Institute of Public Health and foreign data sources are used. The analysis shows great increase of the mortality, due to Covid-19 as well as non-Covid deaths. The provisional data for 2021 shows that total mortality is about 40% higher than in 2019. Besides that, significant changes in the demographic and ethnic structure of deaths happened in 2020 compared to 2019, accompanied with changes in the causes of death. One of the main impacts of Covid-19 in Republic of North Macedonia is the high excessive mortality.
Keywords: mortality; causes of death; Covid-19 pandemic; Republic of North Macedonia